2005
DOI: 10.1007/s10620-005-2703-9
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Hypothyroidism in Patients with Autoimmune Pancreatitis

Abstract: Patients with hypothyroidism had a significantly higher frequency of anti-thyroglobulin antibody (63.6%) than those without hypothyroidism, but showed no differences in other findings, including serum IgG4 concentration. We could find no significant association between any HLA antigens and the hypothyroid state of autoimmune pancreatitis. Conclusions: One quarter of the patients with autoimmune pancreatitis have hypothyroidism that may be independent of the active state of the pancreatic lesion or systemic fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 33 publications
8
70
0
1
Order By: Relevance
“…Patients with IgG4-related disease that included AIP have hypothyroidism in 27% of cases (14) and that finding led investigators to search for a relationship between HT and that systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IgG4-related disease that included AIP have hypothyroidism in 27% of cases (14) and that finding led investigators to search for a relationship between HT and that systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20 % of patients have a history of allergic disorders such as bronchial asthma, chronic sinusitis, and drug allergies. Up to 15 % of patients with IgG4-RD also have hypothyroidism and/or Hashimoto's thyroiditis [26]. Although some patients rarely have other autoimmune diseases (e.g., rheumatoid arthritis and inflammatory bowel disease), they are more likely to be an incidental association with no proven pathogenetic relevance.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Anti-mitochondria antibody (AMA), a specific marker of PBC, is also very rarely detected in AIP patients. It is reported that one fourth of AIP patients show a decrease in thyroid function and 34% and 17% of them are associated with positive anti-thyroglobulin antibody and anti-thyroid peroxidase (TPO) antibody, respectively [54].…”
Section: Antibodiesmentioning
confidence: 99%
“…It disappears shortly after starting steroid treatment (b) retroperitoneal fibrosis [68], tubulointerstitial nephritis [69,70] and interstitial pneumonitis [71,72]. Other lesions reported include hypophysitis [73], chronic thyroiditis [54], pseudotumor of the liver [74,75], gastric ulcer [76], prostitis [77], Schönlein-Henoch purpura and autoimmune thrombocytopenia [78]. It is unknown whether all of them are real complications of AIP.…”
Section: Extrapancreatic Organ Involvementmentioning
confidence: 99%